2019
DOI: 10.1108/bfj-08-2018-0515
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in halal food ecosystems: the case of the United Arab Emirates

Abstract: Purpose The purpose of this paper is to investigate challenges in balancing interoperability, food quality and customer satisfaction in halal food supply chains. Design/methodology/approach The study employed ethnography and grounded theory research methodologies. Research methods were ethnographic content analysis and document content analysis. The research framework encompassed a range of stakeholder groups connected with the halal food supply chain in the United Arab Emirates (UAE), focussing on Islamic j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 59 publications
1
21
0
1
Order By: Relevance
“…Most types of snacks on the market have a halal label because the area around the recreational forest is dominated by Muslim communities (based on secondary data from the local government) (Quantaniah et al 2013). Muslim people will also prefer snack products with halal labels (Efendi et al 2019;Randeree 2019). They will look at the food ingredients listed on the packaging, whether it supports halal products or vice versa (Al-Teinaz 2020).…”
Section: Peanutmentioning
confidence: 99%
“…Most types of snacks on the market have a halal label because the area around the recreational forest is dominated by Muslim communities (based on secondary data from the local government) (Quantaniah et al 2013). Muslim people will also prefer snack products with halal labels (Efendi et al 2019;Randeree 2019). They will look at the food ingredients listed on the packaging, whether it supports halal products or vice versa (Al-Teinaz 2020).…”
Section: Peanutmentioning
confidence: 99%
“…Estimates show that in 2050, Muslims will account for approximately 30% of the world's population. Therefore, the market for halal products has excellent growth prospects (Randeree 2019;Thomas et al 2017). Considering that halal products can also be consumed by non-Muslims (White et al 2018), many food supply chains produce halal products and provide the same products with a halal certification for Muslim consumers and without the certification for other consumers (Alqudsi 2014).…”
Section: Defining Certification Within the Agri-food Fieldmentioning
confidence: 99%
“…De Boni and Forleo (2019) studied trends and prospects for the development of the Halal market for Italian foods and suggested that poor institutional support, lack of rules and financial support are the major issues, which limit the development of the Halal market in Italy. Randeree (2019) used grounded theory research and investigated challenges in balancing interoperability, food quality and customer satisfaction in Halal food supply chains. This study suggested that supply chain intermediaries are challenged in balancing interoperability issues around non-unified global certification standards.…”
Section: Theoretical Backgroundmentioning
confidence: 99%